Answer:
x =-5 and y = -6
Explanation:
In order to get the answer, I used the elimination/addition method
8y-9x= -3 <— I decided to eliminate the y
5y-8x= 10 <— I decided to eliminate the y
5(8y-9x = -3) <— switch up the number of y from the bottom to multiply
-8(5y-8x= 10) <— switch up the number of y from the top to multiply, but have a negative sign to it
So...our new equation will be....
40y - 45x = -15
+ -40y + 64x = -80
________________________
19x = -95
x = -5
8y-9x= -3
8y-9(-5) = -3
8y+45 = -3
- 45 = - 45
8y = -48
y = -6